Analysis of distribution and determining factors for identifying patterns and predicting the risk of stunting - Anggraeny, Rini; Wafiah, Andi; Hengky, Henni Kumaladewi; Febriani Malik, Fivit (Talenta Publisher, 2025)
Stunting remains a major public health problem in many low and middle income countries, including Indonesia. According to the 2022 National Nutrition Status Survey (SSGI), the national prevalence of stunting reached 21.6%, exceeding the World Health Organization threshold of 20% and remaining far from far the 2024 National Medium Term Development Plan (RPJMN) target of 14%. In South Sulawesi, the prevalence was even higher at 35.7%. Stunting not only impairs physical growth but also affects cognitive development, health status, and long-term productivity. This study aimed to anylize the spatial distribution and determinants of stunting by integrating Geographic Information System (GIS)-based spatial analysis with a case-control study design. A total 0f 200 respondents were included, consisting of 100 stunted children (case group) and 100 non stunted children (control group). Primary data were collected and analyzed using bivariate statistical tests, follewed by GIS based mapping to identify high risk areas. The results showed that maternal and child health was significantly associated with stunting, (OR = 0.190; 95% CI: 0.053–0.684; p = 0.011), indicating a protective effect. In contrast, maternal parenting practices and education were not significantly associated with stunting (OR = 2.111; 95% CI: 0.928–4.805; p = 0.108), although a tendency toward increased risk was observed among mothers with poorer parenting practices and lower education levels. In conclusion, the integration of spatial analysis and epidemiological approaches provides a comprehensive understanding of stunting distribution and its determinants. Strengthening maternal and child health remains a key strategy in reducing stunting, particulary in identified high risk area.